Salivary IgA antigliadin antibody as a marker for coeliac disease. Issue 6 (June 1992) - Hakeem, V; Fifield, R; al-Bayaty, H F; Aldred, M J; Walker, D M; Williams, J; Jenkins, H R
Abstract : In recent years, serum antibodies to gliadin (AGA) have been reported to be useful markers of coeliac disease. IgA AGA have also been found in intestinal secretions and saliva in coeliac disease and may offer a convenient, non-invasive screening test. In order to test this hypothesis, salivary and serum AGA were measured in children with coeliac disease proved by biopsy and compared with several control groups. Measurement of salivary IgA AGA provided excellent discrimination between those children with coeliac disease and the control groups, and our study suggests that it may provide a rapid, non-invasive method of screening for this disease before intestinal biopsy.